Menghidupkan Prinsip 3R: Reuse, Reduce, dan Recycle untuk Masa Depan yang Berkelanjutan Di Kelompok Wanita Tani Garuda 12 Cipayung, Ciputat - Rahmi, Cinta; Noor, M. Arief; Sukardi, Sukardi; Mulasih, Siti; Lesmana, Asep Surya; Syahreza, Arief; Nurdin, Nurdin; Tohiroh, Tohiroh; Saefullah, Aep (LPPM STIE Ganesha, 2024)
Protecting the environment is not just a task, but a moral responsibility that must be borne by every individual. However, it is unfortunate that many people still neglect environmental cleanliness, especially in the process of waste management. The 3R principle, which consists of Reuse, Reduce, and Recycle, is an important approach in managing waste and maintaining environmental sustainability. This community service activity aims to raise awareness and understanding of the importance of the 3R principle and creative ways to apply it in daily life. The program involves target partners from the Garuda 12 Women's Farmer Group in Cipayung Village, Ciputat District, South Tangerang City, with a total of 50 participants. The implementation methods include seminars, workshops, and direct practice held over one day on May 19, 2024. In this activity, participants were provided with theoretical explanations as well as practical demonstrations on how to apply the 3R principles in daily activities. The results of the activity showed an increase in participants' awareness and skills in better waste management. Qualitatively, participants demonstrated high enthusiasm and active involvement in discussions and Q&A sessions. Quantitatively, there was a significant increase in participants' understanding of the 3R principles, measured through pre-tests and post-tests. It is hoped that this activity can inspire significant and sustainable behavioral changes in protecting the environment